Flexible Multi-Channel Analog-Frontend for Ultra-Low Power Environmental Sensing - Marcel Jotschke; Peter Reichel; Wilmar Carvajal Ossa; Jeongwook Koh; Torsten Reich; Christian Mayr (IEEE Open Journal of Circuits and Systems)
The trend towards ubiquitous electronics drives the development of autonomous hardware components with longer operating times. This work presents a novel ultra-low power analog sensor frontend (AFE) for environmental sensing applications. Relevant operation parameters like resolution (6 to 13 bit), sample rate (1 to 7.5 kS/s), voltage gain (−6 to 12 dB), transimpedance (1.5 to 12 M $ \boldsymbol {Ω }$ ), and moving average (1 to 128 taps) are real-time programmable. Four input channels are separately configurable to process voltage, current and potentiometric signals of external or internal sources. The flexible channel-wise configuration enables processing of various signal types and therefore offers a versatile solution for sensors from the Internet-of-Things (IoT) market segment. The AFE integrates switched-capacitor amplifiers, 13 bit, 10 kS/s successive approximation analog-to-digital converter (SAR ADC), bias references, oscillator, digital signal pre-processing and communication in a system-on-chip. A novel sensor power regime supports the flexible read-out of commercial IoT sensors, resulting in excellent power consumption. Fabricated samples in 180nm technology show an ultra-low power consumption of $8.8\,μ \text{W}$ . The SAR ADC achieves 10.6 effective bits while consuming $1.8\,μ \text{W}$ , resulting in a Figure-of-Merit of 116.0 fJ/conv.-step. Measurements with commercial sensors prove the AFE’s suitability for an energy-harvester-powered IoT environmental sensor node.